The public value of child-friendly space: Reconceptualising the playground - Pitsikali, Alkistis; Parnell, Rosie; McIntyre, Lesley (ArchNet-IJAR, 2020)
PurposeThe playground is a commonly advised means to integrate children into the public realm of “child-friendly cities”, yet research has tended not to examine it in relation to adjacent public space. This paper aims to understand the extent to which the playground – a socio-spatial phenomenon – facilitates children's integration into the public realm, enabling critical examination of the “child-friendly space” concept.Design/methodology/approachAn ethnographic study was carried out across three sites in Athens, Greece, where typical neighbourhood playgrounds replicate features common across the global north. Methods combined observation (167 h; morning, afternoon, evening), visual-mapping and 61 semi-structured interviews with 112 playground users (including adults and children from the playgrounds and surroundings). Rigorous qualitative thematic analysis, involving an iterative post-coding process, allowed identification of spatial patterns and emergent themes.FindingsFindings reveal perceptions surrounding the protective and age-specific aspects of child-friendly design, limit the playgrounds' public value. However, a paradox emerges whereby the playgrounds' adjacency to public spaces designed without child-friendly principles affords children's engagement with the public realm.Research limitations/implicationsReconceptualisation of the “child-friendly playground” is proposed, embracing interdependence with the public realm – highly significant for child-friendly urban design theory and practice globally. Researchers are encouraged to compare findings in other geographical contexts.Originality/valueThis original finding is enabled by the novel approach to studying the playground in relation to adjacent public realm. The study also offers the first empirical examination of child-friendly city principles – participation in social life and urban play – in a Greek context, addressing a geographical gap in literature on children's everyday spaces.